Modeling and Sustainability Assessment of Outdoor Chlorella vulgaris Cultivation in South Korea for Renewable Bioplastic Feedstock Production. Issue 7 (2022) - Lee, Jeehwan; Heo, Seongmin; Lee, Jay H.
Abstract: UTEX 2714 ( Chlorella vulgaris ) is cultivated outdoors in vertical bubble columns contained within a greenhouse to serve as a renewable blending bioplastic feedstock (BPFS). This application has potential advantages over traditional biofuels due to a simpler downstream process and higher marketability of the bioplastic product (> 1200 USD/ton). To assess sustainability for further scale-up and predict growth for varying seasonal conditions, mathematical modeling of growth kinetics was performed. Pilot plant data for parameter estimations were provided by the Pangyo LNG power plant complex. For early June 2021 during which the data was collected, algae productivity was 0.13 kg/m 3 /day, with the unit cost of production and specific carbon footprint being 2768 USD/ton and 1.33 ton CO2 -eq/ton, respectively. Monthly average productivity dipped to 0.061 kg/m 3 /day in February and peaked at 0.16 kg/m 3 /day in early August. Seasonal variations in temperature and light intensity significantly influenced the economic viability and greenhouse gas emission reducibility of the BPFS process, which highlights the need to improve the accuracy of the growth prediction model and expand the risk assessment scope for guiding future R&D.